PENGEMBANGAN BAHAN AJAR DIGITAL IPAS BERBASIS FLIPBOOK UNTUK MENINGKATKAN HASIL BELAJAR DAN KETERAMPILAN BERPIKIR KRITIS SISWA KELAS IV SEKOLAH DASAR - Dinar Ari Wulan; Hendri Marhadi; Tuti Purwoningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low learning outcomes and critical thinking skills of fourth-grade elementary school students on photosynthesis material caused by limited teaching materials that are less interactive and have not optimally utilized digital media. This study aims to develop and test the feasibility and effectiveness of flipbook-based digital science teaching materials in improving students' learning outcomes and critical thinking skills. The method used is Research and Development (R&D) with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were 18 fourth-grade students of Gebang 2 Masaran Elementary School, with small group tests involving 8 students and large group tests involving all students. Data collection was carried out through observation, teacher and student response questionnaires, pretest-posttest tests, and validation by material experts and media experts. Data analysis used qualitative and quantitative descriptives, including the calculation of average scores and N-Gain. The validation results showed that flipbook-based digital teaching materials were declared suitable for use. The validation of material experts obtained a percentage of 79% (feasible), while the validation of media experts was 78% (feasible). Teacher responses showed a percentage of 80% (adequate). Student responses in the small group test reached 79% (adequate), while in the large group test it increased to 81% (very appropriate). The effectiveness of the teaching materials was shown by an increase in student learning outcomes from an average pretest score of 50.00 to 84.44 in the posttest, with an N-Gain value of 0.69 which is included in the high category. In addition, students' critical thinking skills also increased, from an average score of 8.33 before learning to 15.72 after using flipbook-based digital teaching materials. Based on these results, it can be concluded that the developed flipbook-based digital science teaching materials are declared feasible and effective for use in science learning to improve learning outcomes and critical thinking skills of fourth-grade elementary school students.